Pejabat Residen Bahagian Sri Aman / Ester Endayu Anthony Abell - Anthony Abell, Ester Endayu (University Technology MARA Sarawak, 2016)
Sri Aman Division, formerly known as "Simanggang" or the Second Division was established on 1 June 1873.Nama taken in conjunction with the Sri Aman Sri Aman Declaration historical events, namely the pada21 security pact signed in October 1973 between the government and the official name komunis.Penukaran effective on March 1974.Bahagian Sri Aman was originally composed of four areas, namely Sri Aman, Lubok Antu, Betong District, and District 9 Saratok and small areas including Pantu district, Lingga, Maludam, Engkelili, Spaoh, Debak, Pusa , Kabong and Roban.Selepas declaration of Betong on March 26, 2002, Sri Aman district is composed of 2 and 3 covering a small area Engkilili sub-district, and Lingga Pantu.Kaum Iban are the majority who inhabit large areas in Sri Aman.Kebanyakan areas in Sri Aman division, are accessible by road darat.Namun thus, there is also the rural areas who do not have the communication system and can only be reached by river or sea. Brooke ruled Sarawak government for 100 years from 1841 to 1941. In order to stabilize the chaos caused by war rampant in Sarawak at that time, Rajah Charles Brooke, on June 1, 1873, established three administrative divisions of the First Division (now known as Division Kuching), Part two (Sri Aman) andPart three (Sibu).